IMPROVING ENGINEERING EDUCATION SYSTEM TO ENSURE PERSONNEL TRAINING FOR DEFENSE INDUSTRY - Vyacheslav Kh. Pshikhopov; Evgeny Y. Kosenko (Moscow Polytechnic University, 2016)
The article discusses the ways and means for improving the education process in accordance with the needs of the defense-industrial complex. Determination of the speciallevels of educational qualifications (bachelor, specialist, bachelor-master, specialist-master) is considered as an effective mechanism for organizing specialized education to meet the changing needs of employers. Thus the main focus is made on providing conditions for the advanced development of basic and modern technologies of defense enterprises. Analyzing the existing problematic issues, both from the position of university and from the position of employers, the authors suggest a system of stepwise measures aimed at improvingthe structure of the educational process, development of a system of continuous education, as well as at the formation of an effective mechanism for educational management according with the requirements of employers.